Augmenting the power of online collaboration and innovation through networked learning - Quinton, Stephen; Houghton, P. (Curtin University of Technology, 2005)
Alongside the rapid acceptance of global networked technologies and the omnipresent revolution in information distribution, Information and Communications Technologies (ICT) have spawned hitherto unknown dimensions in human communications and expression that challenge the accepted cultural, educational, and institutional boundaries. Most notably, the convergence of computers and communication technologies has produced 'virtual' networked communities and organisations in many fields of endeavour. A beneficial outcome has been the abolition of time and distance as barriers to worldwide collaboration on a broad range of tasks and activities. As a result, teachers and students located anywhere throughout the globe are now able to 'meet', collaborate, and exchange views at will. The impact of recent technological developments on the way humans interact, construct and apply knowledge is at present unknown, particularly in relation to education. It is known however, that in addition to using printed text, many students are highly proficient in exploiting nonlinear electronic media (hypermedia), and applying interactive annotation and authoring tools as a means of exchanging ideas and generating new knowledge. Learners are now afforded an opportunity to move beyond the linear structure of print and engage in learning activities where they are no longer confined to the passive role of memorisation. To date, educators have grasped little more than a partial insight into the enormous potential of online networking as a productive tool for enhancing learning through collaboration and discussion. The significance of this new potential is accentuated by a marked absence of a theoretical foundation for the design of web-based solutions that may serve as a catalyst for advancing creative learning communities.